Forging the ties the bind : comparing the factors behind electricity market integration in the EU and ASEAN - Boëthius, Gustav (2014)
This paper examines the political forces that drive electricity grid expansion in the European Union (EU) and the Association of Southeast Asian Nations (ASEAN). Although there are a number of short-term political and economic barriers to electricity market integration, there are also compelling economic, environmental and energy security benefits of establishing large-scale and dynamic electricity markets in the long-term. By considering the conceptually unique aspects of the incentives for regional electricity market integration in the EU and ASEAN, the contrast in progress made in establishing regional electricity markets in the two regions is explained. The most important factor accounting for this difference is the fact that there are contrasting energy scenes in the EU and ASEAN. Being a single market consisting predominantly of net energy consumers, and with institutions at the European level to coordinate the decision making process on energy matters, it is relatively easy for the EU to pursue efforts in electricity market integration. In ASEAN, the existence of both energy importers and exporters within the same regional forum makes the establishment of a regional energy grid, which has the ability to increase the production of renewable energy in Southeast Asia much more complex. Moreover, concerns regarding the loss of national sovereignty are a further factor that continues to hamper ASEAN efforts to establish an effective regional electricity market in ASEAN. As the EU member states have already pooled a degree of their sovereignty, and in particular since the Lisbon Treaty made energy a core competency of the European institutions, significant resistance to external intervention in national affairs has largely been avoided.